Design and synthesis of a photoswitchable guanidine catalyst - Viehmann, Philipp; Hecht, Stefan (Beilstein Journal of Organic Chemistry, 2012)
A novel design as well as a straight-forward synthesis for a photoswitchable guanidine catalyst is reported. Intense studies of the photochromic properties demonstrated the reversible switchability of its photosensitive azobenzene moiety. Its activity in the ring-opening polymerization (ROP) of rac-lactide was investigated as well. The obtained results are discussed, and an additional guanidine was synthesized and utilized in the ROP of rac-lactide in order to explain the findings.
Keywords: azobenzenes; guanidines; molecular switches; organocatalysis; photochromism; ring opening polymerization

(untitled) - Russew, M.-M.; Hecht, S. (Adv. Mater., 2010)

(untitled) - Stoll, R. S.; Hecht, S. (Angew. Chem., Int. Ed., 2010)

Photochromism: Molecules and Systems - Dürr, H.; Bouas-Laurent, H. (Elsevier, 2003)

Molecular Switches - Feringa, B. L. (Wiley-VCH, 2001)

Organic Photochromic and Thermochromic Compounds - Crano, J. C.; Guglielmetti, R. J. (Plenum Publishers, 1999)

(untitled) - Peters, M. V.; Stoll, R. S.; Kühn, A.; Hecht, S. (Angew. Chem., Int. Ed., 2008)

(untitled) - Stoll, R. S.; Hecht, S. (Org. Lett., 2009)

(untitled) - Stoll, R. S.; Peters, M. V.; Kuhn, A.; Heiles, S.; Goddard, R.; Bühl, M.; Thiele, C. M.; Hecht, S. (J. Am. Chem. Soc., 2009)

(untitled) - Ueno, A.; Takahashi, K.; Osa, T. (J. Chem. Soc., Chem. Commun., 1981)

(untitled) - Lee, W.-S.; Ueno, A. (Macromol. Rapid Commun., 2001)

(untitled) - Würthner, F.; Rebek, J., Jr (Angew. Chem., Int. Ed. Engl., 1995)

(untitled) - Würthner, F.; Rebek, J. (J. Chem. Soc., Perkin Trans. 2, 1995)

(untitled) - Cacciapaglia, R.; Di Stefano, S.; Mandolini, L. (J. Am. Chem. Soc., 2003)

(untitled) - Sun, X.; Gao, J. P.; Wang, Z. Y. (J. Am. Chem. Soc., 2008)

(untitled) - Dechy-Cabaret, O.; Martin-Vaca, B.; Bourissou, D. (Chem. Rev., 2004)

(untitled) - Pratt, R. C.; Lohmeijer, B. G. G.; Long, D. A.; Waymouth, R. M.; Hedrick, J. L. (J. Am. Chem. Soc., 2006)

(untitled) - Chuma, A.; Horn, H. W.; Swope, W. C.; Pratt, R. C.; Zhang, L.; Lohmeijer, B. G. G.; Wade, C. G.; Waymouth, R. M.; Hedrick, J. L.; Rice, J. E. (J. Am. Chem. Soc., 2008)

(untitled) - Zhang, L.; Pratt, R. C.; Nederberg, F.; Horn, H. W.; Rice, J. E.; Waymouth, R. M.; Wade, C. G.; Hedrick, J. L. (Macromolecules, 2010)

(untitled) - Priewisch, B.; Rück-Braun, K. (J. Org. Chem., 2005)